Design and fabrication of singular phase nanophotonic cavities for phase sensitive hydrogen sensing - Goh, Gordon Jun Sheng (Nanyang Technological University, 2021)
Optical sensors have widely been accepted as a better alternative to electrical sensors for hydrogen sensing. For both optical and electrical sensors, palladium is commonly used for hydrogen sensing due to its high selectivity and response to hydrogen adsorption. There are many different types of optical hydrogen sensor whose transducing technique is based on intensity change, and spectral and angular shift. In this context, we design and fabricate singular phase nanophotonic cavities for phase sensitive hydrogen sensing. More importantly, the proposed hydrogen sensor will in theory have better response time, recovery time and limit of detection than existing hydrogen sensors. In this project, we show the basic concepts of phase sensitive hydrogen sensing by achieving singular phase at the point of darkness. By using variable-angle high resolution spectroscopic ellipsometer, we experimentally demonstrate singular phase in palladium-based cavities at the Brewster angle. Moreover, we show the detection of low concentrations of hydrogen by monitoring the phase shift due to the adsorption hydrogen. This form of hydrogen sensor does not require complex lithography to be fabricated, hence reduce the experimental complexity, and improve the reproducibility.